2004
DOI: 10.1073/pnas.0307812101
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein inhibitor CPI-17 specificity depends on allosteric regulation of protein phosphatase-1 by regulatory subunits

Abstract: Inhibition of myosin phosphatase is critical for agonist-induced contractility of vascular smooth muscle. The protein CPI-17 is a phosphorylation-dependent inhibitor of myosin phosphatase and, in response to agonists, Thr-38 is phosphorylated by protein kinase C, producing a >1,000-fold increase in inhibitory potency. Here, we addressed how CPI-17 could selectively inhibit myosin phosphatase among other protein phosphatase-1 (PP1) holoenzymes. PP1 in cell lysates was separated by sequential affinity chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 41 publications
2
95
0
2
Order By: Relevance
“…Consistent with previously published structural data, Fig. 4C demonstrates that CPI-17 physically interacts with PP1␣, evaluated by co-immunoprecipitation, which leads to inhibition of phosphatase activity (27). In addition to being potentiated by PKC, CPI-17 has also been shown to be activated by ROCK and PKN (28,29).…”
Section: Depolarization Enhances Mef2-dependent Gene Expression Throusupporting
confidence: 89%
“…Consistent with previously published structural data, Fig. 4C demonstrates that CPI-17 physically interacts with PP1␣, evaluated by co-immunoprecipitation, which leads to inhibition of phosphatase activity (27). In addition to being potentiated by PKC, CPI-17 has also been shown to be activated by ROCK and PKN (28,29).…”
Section: Depolarization Enhances Mef2-dependent Gene Expression Throusupporting
confidence: 89%
“…Thus, MYPT1 is not essential for phosphatase activity directed toward phosphorylated RLC. We, therefore, suggest that the remaining PP1c␦ is sufficient to dephosphorylate phosphorylated RLC, although the activity is less than in the holoenzyme (36).…”
Section: Discussionmentioning
confidence: 75%
“…We previously found in rat ileal smooth muscle that carbachol-induced contraction is mainly associated with phosphorylation of CPI-17 at Thr38 rather than MYPT1 phosphorylation at Thr696 [20]. Phosphorylation of CPI-17 due to receptor stimulation is reportedly mediated by PKC, as well as by ROCKs and PKN via RhoA activation [7,10,15,16,20]. In the present study, we demonstrated that carbachol-induced increases in CPI-17 phosphorylation were significantly reduced in organ-cultured ileal tissue treated with 17-estradiol, but no changes in total CPI-17 protein expression were noted.…”
Section: Carbachol-induced Contraction Decreased With Upregulation Ofmentioning
confidence: 97%